2022
DOI: 10.3389/fpsyt.2022.792206
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of Adult ADHD Symptoms and Problematic Internet Use and Its Links With Impulsivity, Emotion Regulation, Anxiety, and Depression

Abstract: The co-occurrence of attention-deficit/hyperactivity disorder (ADHD) and problematic Internet use (PIU) is associated with increased severity of PIU and poorer treatment outcomes. The main objective of this study was to examine the association between PIU and adult ADHD symptoms and determine whether adult ADHD symptoms were a predictor of PIU in the general adult population. We also examined the potential mediating role of the dimensional psychopathological factors, including anxiety, depression, impulsivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…The results of our research is consistent with previous study, which proved that impulsivity can predict the onset of depression as a distinct personality factor in adults by logistic regression model [54]. Individuals who have difficulties in emotion regulation are at significant risk of using inappropriate strategies to cope with life events [92]. Past research found that the higher emotion dysregulation group scored significantly higher on impulsivity [93].…”
Section: Impulsivity and Depressive Symptoms Are Chain Mediators In T...supporting
confidence: 91%
“…The results of our research is consistent with previous study, which proved that impulsivity can predict the onset of depression as a distinct personality factor in adults by logistic regression model [54]. Individuals who have difficulties in emotion regulation are at significant risk of using inappropriate strategies to cope with life events [92]. Past research found that the higher emotion dysregulation group scored significantly higher on impulsivity [93].…”
Section: Impulsivity and Depressive Symptoms Are Chain Mediators In T...supporting
confidence: 91%
“…According to Billieux et al (2012), urgency could predict severity of addictive disorders, whereas lack of premeditation could predict engagement in harmful behaviors. Moreover, the literature suggested that urgency and lack of perseverance could mediate the association between adult ADHD and addictive behaviors (El Archi et al, 2022;Fatseas et al, 2016;Grall-Bronnec et al, 2011;Yen et al, 2017). Thus, the UPPS-P model of impulsivity seems to be a suitable model to assess impulsivity in individuals with both adult ADHD and behavioral addiction.…”
Section: Introductionmentioning
confidence: 99%
“…The present study also found evidence for the positive association between maladaptive daydreaming and problematic Twitch use, suggesting that individuals with excessive daydreaming activity may be more prone to behavioral addictions. More recent studies have found that symptoms of attention-deficit/hyperactivity disorder (ADHD), depression, and impulsivity predicted problematic Internet use (see El Archi et al, 2022). Individuals with symptoms of problematic Internet use and ADHD reported using more ineffective coping strategies (Corbisiero et al, 2013; Koronczai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, individuals with ADHD are more vulnerable to emotional difficulties (Corbisiero et al, 2013) and are more prone to excessive daydreaming to cope with negative emotions (Musetti et al, 2022). Therefore, these individuals are at a higher risk for disorders on the impulsive-compulsive spectrum such as maladaptive daydreaming (Somer, Somer, Jopp, et al, 2016) and behavioral addictions (El Archi et al, 2022). However, a recent study has found that only 20%–23% of adults diagnosed with ADHD were also maladaptive daydreamers, suggesting that the two constructs have only a modest overlap (Theodor-Katz et al, 2022).…”
Section: Discussionmentioning
confidence: 99%